The Procurement Strategy for Recycled Paper: Case Study at PT. Kertas Makmur Abadi (PT KMA) - Maria Cynthia; Erlinda Yunus (School of Business, IPB University (SB-IPB), 2024)
Background: Procurement practices nowadays has transcended from merely operational to a strategic objective in business. Studies have shown that procurement strategy create optimal value, increase competitiveness, and company resiliency during crisis if it is aligned with the overall organization's strategy, vision, goals, and value proposition to achieve company goals.Purpose: This research aims to develop a sustainable procurement strategy to ensure the availability of PT Kertas Makmur Abadi (an alias, hereafter named PT KMA)’s recycled paper in 2024-2026. Design/methodology/approach: This study used qualitative methods as the basis of research methods, namely questionnaires, interviews, observation, and analytical studies with existing theories. To ensure the availability of recycled paper, the company had to design a procurement strategy starting with determining the criteria used to select and evaluate suppliers. The determination of criteria was carried out using a pairwise comparison technique suggested by the Analytical Hierarchy Process. The design of the recycled paper procurement strategy was obtained from procurement portfolio analysis and market analysis using the Kraljic Portfolio Matrix method.Findings/results: The results showed that recycled paper was a strategic material with high supply risk and profit impact, and therefore needed a partnership strategy. This study further resulted in a partnership strategy that comprised three procurement programs: exploitation, balanced, and diversification.Conclusion: Therefore, the three programs are the most appropriate in procuring recycled paper for PT KMA for the 2024-2026 period to ensure the continued availability of PT KMA recycled paper.Originality/value (State of the art): The current state of research emphasizes integrating advanced analytical methods like AHP and the Kraljic Portfolio Matrix with sustainability principles to develop an effective procurement strategy. The strategy addresses recycled paper's supply risk and profit impact and sets the foundation for sustainable procurement practices within organizations. Keywords: analytical hierarchy process, kraljic portfolio matrix, procurement strategy recycled paper, sustainable procurement